The Relationship Between Uric Acid Levels and The Progression of End-Stage Renal Disease : A Systematic Review - Lilis Haryani (International Medical Journal Corp. Ltd, 2026)
Introduction: Elevated serum uric acid (SUA) is associated with chronic kidney disease (CKD) progression, but large trials of urate-lowering therapy (ULT) show conflicting results. This systematic review synthesizes evidence on the relationship between SUA levels and end-stage renal disease (ESRD) progression. Methods: We screened longitudinal studies (RCTs, etc) examining SUA as a predictor or intervention for CKD progression to ESRD (eGFR <15 mL/min/1.73m², dialysis, or transplantation). Data extraction focused on SUA measurement, ESRD outcomes, confounders, and ULT effects. Results: Among 80 included sources (total >3.4 million patients), observational studies consistently showed that hyperuricemia predicts ESRD (HR 1.53–2.84) and rapid eGFR decline (OR 1.38–3.77) with dose-response relationships (1,2,5,18). The association was nonlinear: hazard of kidney failure increased sharply above 11 mg/dL, while mortality showed a U-shaped relationship with nadir at 5 mg/dL (6). Large RCTs (FEATHER, CKD-FIX, PERL) found no significant benefit of ULT on eGFR slope, but meta-analyses of smaller trials reported modest eGFR preservation (mean difference 1.81–4.10 mL/min/1.73m²) (1,8,9). Achieving SUA <6 mg/dL, not merely initiating ULT, was associated with 37–63% fewer renal events (11,12). Effect modification by baseline CKD stage, proteinuria, sex, and disease etiology was prominent. Discussion: The observational-evidence and RCT-evidence discordance is explained by low progression rates in control arms, insufficient target SUA achievement, and population heterogeneity. ULT appears most beneficial in early CKD (stages 1–3), rapidly progressive disease, and when SUA target <6 mg/dL is reached. In advanced CKD, very low SUA may be harmful. Conclusion: Elevated SUA is a robust independent risk factor for CKD progression, but ULT benefits are conditional on patient selection and target attainment. Future trials should enroll high-risk, hyperuricemic patients with progressive disease and titrate to SUA <6 mg/dL.